2015
DOI: 10.4269/ajtmh.15-0080
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in Zhejiang Province, China, from 2005 to 2014

Abstract: To summarize the changing epidemiological characteristics of malaria in Zhejiang Province, China, we collected data on malaria from the Chinese Notifiable Disease Reporting System (NDRS) and analyzed them. A total of 2,738 malaria cases were identified in Zhejiang Province from 2005 to 2014, of which 2,018 were male and 720 were female. Notably, only 7% of malaria cases were indigenous and the other cases were all imported. The number of malaria cases increased from 2005 to 2007, peaked in 2007, and then decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, African countries spread the infection to other countries, including France (> 2500), China (> 2000), UK (approximately 1500), and Germany (> 500) in 2017 [1,20]. Zhejiang province, located in southeast China, had several cases of P. falciparum malaria imported from Africa in recent years [21,22]. The current study evaluated drug resistance markers of P. falciparum infections predominantly from Africa using molecular assays to advance drug policies against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, African countries spread the infection to other countries, including France (> 2500), China (> 2000), UK (approximately 1500), and Germany (> 500) in 2017 [1,20]. Zhejiang province, located in southeast China, had several cases of P. falciparum malaria imported from Africa in recent years [21,22]. The current study evaluated drug resistance markers of P. falciparum infections predominantly from Africa using molecular assays to advance drug policies against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to 2010, an increase of 24.6 and 44.9% were observed, respectively [39]. Available evidence indicated that P. falciparum was mostly imported via Chinese people returning from Africa [17, 38, 40–44]. …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the data before 2004 were collected from annual paper-based surveillance data and compilation of information on the elimination of malaria (Wang et al 2010, Chen et al 2015. Since 2004, each case that has been obtained through the Infectious Diseases Information Reporting Management System (IDIRMS; http://chinacdc.cn) has been subjected to rigorous quality control reviews (Kong et al 2017, Feng et al 2018.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Indigenous cases refer to malaria transmitted by mosquitoes in endemic areas of China (Chen et al 2015). Imported malaria cases must meet all of the following criteria: a diagnosis of malaria and a travel history during the malaria transmission season and symptom development within 1 month after returning to China during the local transmission season (Kong et al 2017).…”
Section: Case Typesmentioning
confidence: 99%